(untitled) (Research, Society and Development, 2022)
Abstract: The aim of this review is to understand the feasibility and potential clinical utility of US in measurements of the quadriceps muscles in patients with COPD. A total of 217 studies were identified and after applying the inclusion criteria, 12 were selected. The data were systematically searched by two independent reviewers. Of the included articles, five evaluated the maximal voluntary contraction of the quadriceps muscle and the Transverse Section Area (TSA) measured by US, of these, 4 found a remarkably reduced strength in COPD and in one article, it was described that this reduction occurs in all grades of the disease. Moreover, the greater the thickness of the quadriceps, the greater the maximum voluntary contraction of this musculature, however, the TSA is reduced in these patients when compared to healthy individuals. Thus, it is suggested that the AST, evaluated by US, can be used to assess the presence and/or severity of musculoskeletal dysfunction in these patients. The sonographic evaluation of the quadriceps in patients with COPD may provide a safe, effective, low-cost, reliable and reproducible evaluation, allowing the identification and monitoring of peripheral muscle dysfunction in this population, even when compared with other strategies.